MHC Class II Protein Turnover In vivo and Its Relevance for Autoimmunity in Non-Obese Diabetic Mice - Busch, Robert; De Riva, Alessandra (Frontiers in Immunology, 2013)
MHCII proteins are loaded with endosomal peptides and reside at the surface of antigen-presenting cells (APCs) for a time before being degraded. In vitro, MHCII protein levels and turnover are affected by peptide loading and by rates of ubiquitin-dependent internalization from the cell surface, which is in turn affected by APC type and activation state. Prior work suggested that fast turnover of disease-associated MHCII alleles may contribute to autoimmunity. We recently developed novel stable isotope tracer techniques to test this hypothesis in vivo. In nonobese diabetic (NOD) mice, a model of type 1 diabetes (T1D), MHCII turnover was affected by APC type, but unaffected by disease-associated structural polymorphism. Differences in MHCII turnover were observed between NOD colonies with high and low T1D incidence, but fast turnover was dispensable for autoimmunity. Moreover, NOD mice with gene knockouts of peptide loading cofactors do not develop T1D. Thus, fast turnover does not appear pathogenic, and conventional antigen presentation is critical for autoimmunity in NOD mice. However, shared environmental factors may underpin colony differences in MHCII protein turnover, immune regulation, and pathogenesis.